Enhancing skull base tumor management: the combination of 3D printing technology and endoscopic surgical techniques - Xiao Li; Peng Gao; Angsi Liu; Fuxing Zuo; Ke Hu; Yang Wang; Haiyan Li; Jianxin Kong; Xueji Li (3D Printing in Medicine)
Abstract Object 3D printing technology stands as a transformative force in medicine, offering outstanding precision and personalization in surgical planning, patient education, and the development of anatomical models for complex procedures. This paper aims to explore the application experiences of 3D printing in endoscopic skull base tumor surgeries, evaluating the impact and effectiveness of 3D-printed models in enhancing both surgical simulations and anatomical learning in the field of neurosurgery for skull base tumors. Method From October 2015 to March 2019, our institution enrolled five patients for whom individualized 3D-printed models were created, utilizing different printing techniques and materials. These models served a critical role in preoperatively determining the most effective surgical approaches. Additionally, they were instrumental in facilitating endoscopic surgery simulations and enhancing anatomical education. To assess the utility of these 3D models, nine neurosurgeons from our institution were surveyed using the Likert scale questionnaire, providing valuable insights into the effectiveness of 3D printing in clinical applications of neurosurgery. Result Our team successfully printed five complex skull base tumor models using 3D printing technology, which significantly improved the outcome of skull base tumor diagnosis and treatment. An evaluation of the Likert scores revealed that model 4, crafted using mixed photosensitive resin, was particularly effective for surgical simulation and anatomical education. The mean (standard deviation, SD) 3D printing time is 16.3 (5.54) hours, and the mean (SD) printing cost is 4,500 (1132.88) RMB, demonstrating the efficiency of this approach. Conclusion 3D printing technology emerges as a highly valuable asset in the realm of endoscopic surgery for skull base tumors. Its rapid production turnaround allows for urgent surgical preparation needs. Additionally, this technology optimizes the learning curve for clinical pathological anatomy and endoscopic surgery. This combination advances surgical practices and training, particularly in the challenging domain of skull base neurosurgery.